Chromatographic methods for the isolation, separation and characterisation of dissolved organic matter. Issue 9 (20th August 2015) - Sandron, Sara; Rojas, Alfonso; Wilson, Richard; Davies, Noel W.; Haddad, Paul R.; Shellie, Robert A.; Nesterenko, Pavel N.; Kelleher, Brian P.; Paull, Brett
Abstract : This review presents an overview of the separation techniques applied to the complex challenge of dissolved organic matter characterisation. Abstract : This review presents an overview of the separation techniques applied to the complex challenge of dissolved organic matter characterisation. The review discusses methods for isolation of dissolved organic matter from natural waters, and the range of separation techniques used to further fractionate this complex material. The review covers both liquid and gas chromatographic techniques, in their various modes, and electrophoretic based approaches. For each, the challenges that the separation and fractionation of such an immensely complex sample poses is critically reviewed.